Comparing Surface and Stratospheric Impacts of Geoengineering With Different SO2 Injection Strategies. Issue 14 (21st July 2019) - Kravitz, Ben; MacMartin, Douglas G.; Tilmes, Simone; Richter, Jadwiga H.; Mills, Michael J.; Cheng, Wei; Dagon, Katherine; Glanville, Anne S.; Lamarque, Jean‐Francois; Simpson, Isla R.; Tribbia, Joseph; Vitt, Francis
Abstract: Geoengineering with stratospheric sulfate aerosols can, to some extent, be designed to achieve different climate objectives. Here we use the state‐of‐the‐art Community Earth System Model, version 1, with the Whole Atmosphere Community Climate Model as its atmospheric component (CESM1(WACCM)), to compare surface climate and stratospheric effects of two geoengineering strategies. In one, SO2 is injected into the tropical lower stratosphere at the equator to keep global mean temperature nearly constant under an RCP8.5 scenario, as has been commonly simulated in previous studies. In another, the Geoengineering Large Ensemble (GLENS), SO2 is injected into the lower stratosphere at four different locations (30°N/S and 15°N/S) to keep global mean temperature, the interhemispheric temperature gradient, and the equator‐to‐pole temperature gradient nearly unchanged. Both simulations are effective at offsetting changes in global mean temperature and the interhemispheric temperature gradient that result from increased greenhouse gases, but only GLENS fully offsets changes in the equator‐to‐pole temperature gradient. GLENS results in a more even aerosol distribution, whereas equatorial injection tends to result in an aerosol peak in the tropics. Moreover, GLENS requires less total injection than in the equatorial case due to different spatial distributions of the aerosols. Many other aspects of surface climate changes, including precipitation and sea ice coverage, also show reduced changes in GLENS as compared to equatorial injection. Stratospheric changes, including heating, circulation, and effects on the quasi‐biennial oscillation are greatly reduced in GLENS as compared to equatorial injection. Key Points: Tropospheric and stratospheric side effects of equatorial solar geoengineering are reduced if nonequatorial injections are applied Some residual temperature effects from equatorial injection can be offset with multiple injection locations There are still residuals in surface climate and the stratosphere that cannot be offset with four injection locations